A Christian Ethical Perspective on Extramarital Sexual Practices in the Ana Bui Pa Kepue Culture of the Sabu Community - Widodo, Priyantoro; Sembiring, Naulia Julitandari; Karong, Franklin (Sekolah Tinggi Teologi Simpson Ungaran, 2026)
Premarital sex in the Sabu tribe's Ana Bui Pa Kepue culture posed social challenges due to lenient customary sanctions, conflicting with Christian ethics on sexual holiness; this study addressed the knowledge gap in transforming such cultural practices through biblical principles. The study examined Christian ethical perspectives on premarital sex within the Ana Bui Pa Kepue tradition to propose cultural reconstruction. The research focused on the Sabu community in Sabu Raijua Regency, East Nusa Tenggara, Indonesia. A literature review was conducted, supplemented by secondary interview data from customary leaders and pastors, to analyze cultural practices and Christian ethics descriptively. Sabu customary law inconsistently sanctioned premarital sex leading to Ana Bui Pa Kepue children (12 cases, 2019-2022), viewing them as blessings, while Christian ethics deemed such acts sinful. Christian ethics condemned premarital sex as violating God's holiness; recommendations included church collaboration with elders for stricter sanctions and comprehensive spiritual education for youth. The study offered practical strategies for cultural transformation, enhancing Christian influence on Sabu tradition to deter premarital sex and promote biblical sexuality.